Penerapan Model Multiple Representation Berbasis Somatis, Auditory, Visual, Intelektual terhadap Self Efficacy Peserta Didik - Maulita Anggraini*; Ismul Huda; Safrida Safrida; Hafnati Rahmatan; Djufri Djufri (Jurnal Pendidikan Sains Indonesia, 2022)
Low self-efficacy is due to the fact that the learning process only focuses on the material with rote concepts, so that students are not given the opportunity to practice self-confidence by conducting group discussions and making observations about the circulatory system so that students are less confident in their opinions, ask and answer questions. In fact, the biology learning process in schools does not encourage students to practice self-efficacy. The approach used in learning does not direct students to practice self-confidence. The purpose of this study was to determine the difference between the application of SAVI-based multiple representation and SAVI learning on self-efficacy on the material of the circulatory system in class 11th SMAN Bener Meriah.The method used is quasi-experimental, with non randomized  control group pretest posttest design. The population in this study were 156 students of class 11th MIPA, amounting to 487 students, while the sample was 120 taken by purposive sampling.. The instrument used in this study is a test consisting of a self-efficacy questionnaire. Data analysis using Anova test. Results of the study show that there are differences in the self-efficacy of students who are taught using SAVI-based multiple representation learning and SAVI learning on self-efficacy on the material of the circulatory system at SMAN Bener Meriah. Conclusion: the application of SAVI-based multiple representation is effective in increasing students' self-efficacy.